The African indigenous churches' spiritual resources for democracy and social cohesion - Masondo, Sibusiso T. (Verbum et ecclesia, 2014)
This article outlines resources possessed by the African indigenous churches (AICs) that help them engage with the democratic dispensation and could be used to foster social cohesion in South Africa. It starts off with the premise that social cohesion is that which holds the nation together. The South African rainbow-nation narrative tended to focus on tolerance and there cognition of diversity as strength. Tolerance does not address the fundamental issues that would facilitate cohesion. The idea of cultural justice as advocated by Chirevo Kwenda is seen as the most useful tool to move forward. Cultural justice ensures that all citizens are able to draw on their cultural resources without any fear of being discriminated against. The AICs have an assortment of resources at their disposal that are drawn from African religion,Christianity and Western culture. These resources enable AIC members to appreciate being African and Christian, as well as being South African.